Un occhio al mercato e uno alla morale sessuale: la censura preventiva dei copioni e l’horror italiano (1956-1974) (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
The article deals with a form of film censorship enacted from the late 1910s to the mid- 1970s by the Italian state: the so-called “preventive censorship”, i. e. the pre-shooting check of the screenplays that Italian producers wanted to turn into movies. In particular, the article focuses on the preventive censorship of Italian horror cinema, showing that, in addition to fighting obscene representations of the sexual sphere, the Italian state was an attentive observer of the horror business from 1956 (when the first Italian horror film was put into production) to 1973-1974 (when preventive censorship was discontinued).
Keywords: censorship; Italian horror cinema; obscenity; screenplay; sex